Primary School Teachers’ Attitudes Towards The Training Program For The Sustainable Educational Development Theory Proposed In Developing Electronic Professional Competencies - et.al, Mr. Raed Ramthan Al- Tamimi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research conducts the primary school teachers 'attitudes towards the training program for the theory of the proposed sustainable educational development in the development of professional electronic competencies. The sample of the research consisted of 286 teachers accounted for ( 71 %) 123 males and (163 ) females, who are studying at the primary schools in Rifai at the Directorate of Education in Dhi Qar province, who were chosen purposely, The researchers have adopted the descriptive approach, to achieve the aims of the study, the researchers prepared a scale measure of trends consisted of (30) , items. The validity and reliability of the scale was verified, and the statistical analysis package SPSS was approved to extract the results. The results showed: The attitudes of primary school teachers' towards the training program for the theory of sustainable educational development proposed in developing electronic professional competencies from the teachers ’point of view came in a high degree. “There are statistically significant differences at the level of significance (α = 0.05on the trends of primary school teachers towards the training program for the theory of sustainable educational development proposed in the development of electronic professional competencies according to the difference of sex in favor of females. The absence of statistically significant differences at the level of significance α = 0.05 In the attitudes of primary school teachers towards the training program for the proposed sustainable educational development theory in developing electronic professional competencies according to an experience variable. The research recommended the following: Making an encouragement reward or an effort appraisal letter to teachers who attend training programs. Conducting an annual competition for the ideal teacher to participate in training programs, in order to help them in continuous giving and create a spirit of competition among them.